LEGAL REGULATION OF AUTONOMOUS TECHNICAL MEANS: MAIN CHALLENGES AND RELATED APPROACHES - Kuteynikov, Dmitry; Izhaev, Osman; Lebedev, Valerian; Zenin, Sergey (Revista Inclusiones, 2020)
The article studies some legal issues associated with the newly formed ability of technical means (physical and virtual entities) to independently make legally relevant decisions. The authors of the article have considered the issues of legal identity, algorithmic transparency and accountability, the atmosphere of trust, moral choice and emotional connection between a person and a machine since they are interdependent and somehow affect all types of autonomous technical means. This article proves that autonomous technical means resulted from the Fourth Industrial Revolution are qualitatively different from traditional objects of law (material and non-material). While preparing the article, the authors used methods of collecting and studying isolated facts, generalization, scientific abstraction, legal methods and methods of objectivity, specificity and pluralism. They have concluded that the existing approaches to the legal regulation of autonomous technical means depend on the type of technology, type of technological products or their field of application. The article proposes an alternative approach that develops new legal regulation based on cross-cutting legal issues arising from the fact that modern technical means become autonomous. This approach enables to put forward and substantiate the following thesis: to establish stable and balanced regulation, it is advisable to develop a legal regime that provides for specific control over legal relations and a special set of legal means.